One-Step Synthesis of 5-Substituted 1H-Tetrazoles from an Aldehyde by Reaction with Acetohydroxamic Acid and Sodium Azide under Bi(OTf)3 Catalysis - Sridhar, Madabhushi; Mallu, Kishore Kumar Reddy; Jillella, Raveendra; Godala, Kondal Reddy; Beeram, China Ramanaiah; Chinthala, Narsaiah (Synthesis, 2013)
An efficient one-step method for the synthesis of 5-substituted 1H-tetrazoles from aldehydes by reaction with acetohydroxamic acid and sodium azide using bismuth(III) triflate as the catalyst is described.
Keywords: aldehydes; 5-substituted 1H-tetrazoles; sodium azide; bismuth(III) triflate; catalysis